Um diálogo entre Freud e Lacan fundamentado no caso "o pequeno Hans" - Bonfim, Leilane Gabriela de Souza (2015)
This work has dealt with the clinical Little Hans case - statement by Freud in 1909 - and aims to bring the dialogue between this theoretical and Jacques Lacan, with prints and case analysis. Specifically, the study aims to provide for the issue of child psychoanalysis and addressing the problem of phobia while symptomatic output. Considering the clinic with children as contemporary practice of psychoanalysis, there was a theoretical study, whose methodological dynamics was the literature, using mainly from Freud´s texts and Lacan. Therefore, the work is divided into three sections. The first brings the issue of child psychoanalysis, highlighting as it reaches the place of subject of desire and law, making it therefore possible to be analyzed. In addition, support for the next chapter in this first are brought some positions and functions assumed by the child in the family dynamics. The second chapter develops the dialogue between Freud and Lacan about Hans case, presenting the facts following the case, the chronology, the directions of Freud and Lacan considerations. Are treated some issues such as the relationship between Hans and his mother, the question of the paternal function, as well as the complex of Oedipus and castration in Hans. Finally, the third chapter is the phobia as symptomatic output, serving Hans as the means possible so that it is positioned in the world and enter in the symbolic order. Thus, issues are worked that concern the phobia, such as anxiety, anguish, symptomatic formation and its prospects and the specific clinical case, the focus on substitutive function assumed by the phobic symptom on the limping paternal function. We conclude the work by pointing out some directions for the relationship between the current children´s clinic and the symptom.